2023
DOI: 10.3389/fimmu.2023.1277243
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of traditional Chinese medicine monomers and compound prescriptions to boost cancer immunotherapy

Keyan Miao,
Weici Liu,
Jingtong Xu
et al.

Abstract: At present, cancer is the largest culprit that endangers human health. The current treatment options for cancer mainly include surgical resection, adjuvant radiotherapy and chemotherapy, but their therapeutic effects and long-term prognosis are unsatisfactory. Immunotherapy is an emerging therapy that has completely transformed the therapeutic landscape of advanced cancers, and has tried to occupy a place in the neoadjuvant therapy of resectable tumors. However, not all patients respond to immunotherapy due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 150 publications
(182 reference statements)
0
2
0
Order By: Relevance
“…Notably, we exposed a plausible interaction between HMMR and AURKA, resulting in an elevation of AURKA protein levels. This augmentation subsequently triggered the mTORC2/AKT pathway, as proved in the case of prostate cancer (Miao et al, 2023). Therefore, we hypothesized that HMMR could be targeted through mTOR, which serves as a critical mediator in advancing the progression of breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, we exposed a plausible interaction between HMMR and AURKA, resulting in an elevation of AURKA protein levels. This augmentation subsequently triggered the mTORC2/AKT pathway, as proved in the case of prostate cancer (Miao et al, 2023). Therefore, we hypothesized that HMMR could be targeted through mTOR, which serves as a critical mediator in advancing the progression of breast cancer.…”
Section: Discussionmentioning
confidence: 91%
“… 8 More and more studies have confirmed that TCM can enhance anti-tumor effects by regulating the immune system. 9 , 10 The aim of this study is to introduce how immune cells and non-immune cells in TME promote tumor progression, and to summarize the research progress of TCM in regulating TME.…”
Section: Introductionmentioning
confidence: 99%